AB0105 CHECKPOINT MOLECULES AND PREGNANCY: ENHANCED SPD-L1 PREDICTS FLARE IN RA PREGNANCY AND POSTPARTUM. (2nd June 2020) - Stefanski, A. L.; Eriksson, K.; Zbinden, A.; Villiger, P.; Förger, F.
Abstract : Background: Rheumatoid arthritis (RA) is a female-predominant autoimmune disease that may affect women in childbearing age, making family planning an important issue for their life. There is a need for better understanding the mechanisms modulating RA in pregnancy and develop prognostic marker regarding adverse pregnancy outcome such as reduced birth weight and preterm delivery. As a crucial organ for peripheral tolerance during pregnancy, the placenta is expressing constitutively programmed cell death ligand 1 (PD-L1), major ligand of the inhibitory receptor PD-1 (Zhang et al, 2015). We hypothesize that the PD-1 pathway plays a central inhibitory role in regulating the course of the disease and pregnancy outcome in RA. Objectives: To investigate the relationship between PD-1 pathway, disease activity during pregnancy/postpartum and pregnancy outcome in RA. Methods: We measured soluble PD-1 and PD-L1 levels by ELISA in serum samples of 27 pregnant RA patients and 25 healthy pregnant controls at different time points during pregnancy and postpartum. As for pregnancy controls, we analyzed serum samples from 28 non-pregnant RA patients and 18 non-pregnant healthy controls. The data was analyzed in correlation with disease activity (measured by DAS28-CRP) and pregnancy outcome (defined as preterm delivery and birth weight). Statistics were calculated by Mann-Whitney U test and Wilcoxon test, correlations by Spearman rank test. Results: In healthy pregnancy, sPD-L1 increases significantly in the 1 st trimester (p = 0, 0198) and decreases significantly postpartum (p = 0, 0029). sPD-L1 values are higher in non-pregnant RA patients compared to non-pregnant healthy controls (p = 0, 047) and there are no significant changes during RA pregnancy. Postpartum sPD-L1 values are significantly higher in RA patients compared to healthy controls (p = 0, 0014), Fig. 1 . Notably, regarding disease activity, we noticed a significant positive correlation between the overall sPD-L1 values in RA and DAS28-CRP (p= 0.0104), Fig. 2 . No significant correlation was seen between sPD-L1, birth weight and preterm delivery. For sPD-1 we focused on 3 rd trimester and postpartum, however, there was no difference between healthy controls and RA patients and no correlation with disease activity or pregnancy outcome. Conclusion: In healthy pregnancy, we observed an increase of sPD-L1, which decreases after delivery. This supports the hypothesis, that PD-1 pathway may be involved in shaping the physiological fetal-maternal tolerance. In RA higher sPD-L1 values are measured already in non-pregnant patients compared to healthy controls and there is no physiological decrease postpartum. Intriguing, sPD-L1 correlates positively with RA disease activity, reflecting a possible functional antagonism towards the inhibitory function of membrane bound PD-L1 molecules. However, the detailed function of sPD-L1 need to be further delineated. Nevertheless, sPD-L1 may have the potential to serve as prognostic marker for flares in RA pregnancy. Regarding the rather rarely observed adverse pregnancy outcome, larger cohorts need to be investigated. References: [1]Zhang YH, Tian M, Tang MX et al. Recent Insight into the Role of the PD-1/PD-L1 Pathway in Feto-Maternal Tolerance and Pregnancy. Am J Reprod Immunol. 2015 Sep;74(3):201-8. Disclosure of Interests: Ana-Luisa Stefanski: None declared, Klara Eriksson: None declared, Astrid Zbinden: None declared, Peter Villiger Consultant of: MSD, Abbvie, Roche, Pfizer, Sanofi, Speakers bureau: Roche, MSD, Pfizer, Frauke Förger Grant/research support from: Unrestricted grant from UCB, Consultant of: UCB, GSK, Roche, Speakers bureau: UCB, GSK